Analisis Yuridis Kekosongan Hukum Batas Waktu Penanganan Kanker dalam Sistem Rujukan BPJS Kesehatan - Jasmine Layla Praspa; Sapto Hermawan; Abdul Kadir Jaelani (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
Cancer is a time-critical disease where treatment delays severely threaten patient survival. Although the 1945 Constitution of the Republic of Indonesia and the Health Law guarantee the right to quality healthcare, the National Health Insurance referral system implemented by BPJS Kesehatan currently faces a legal vacuum. This study aims to analyze the juridical urgency of the legal vacuum regarding the time limit for cancer treatment within the BPJS Kesehatan referral system, evaluated from the perspective of legal certainty and patients' constitutional rights. This normative legal research employs statutory and conceptual approaches. Data were collected through library research and analyzed using the deductive syllogism method. The findings reveal regulatory inconsistencies, particularly in BPJS Kesehatan Regulation Number 3 of 2024, which disrupts the referral chain without establishing binding clinical time limits for healthcare facilities. This absence of technical instruments destroys the hierarchy of legal certainty, leaving healthcare facilities trapped merely in administrative compliance. Consequently, patients endure fatal risks of delayed medical interventions due to prolonged waiting lists. The study implies that the government must immediately enact operational technical regulations stipulating absolute time limits for medical referrals, from diagnosis to treatment execution, to guarantee legal certainty and protect cancer patients in Indonesia.